2022
DOI: 10.3390/math10101709
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Mathematical Model of the Dissemination Route of Short-Term Fund-Raising Fraud

Abstract: To effectively protect citizens’ property from the infringement of fund-raising fraud, it is necessary to investigate the dissemination, identification, and causation of fund-raising fraud. In this study, the Susceptible Infected Recovered (SIR) model, Back-Propagation (BP) neural network, Fault tree, and Bayesian network were used to analyze the dissemination, identification, and causation of fund-raising fraud. Firstly, relevant data about fund-raising fraud were collected from residents in the same area via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Instead, we should remember the adage that scientists who are looking for extraterrestrial life sometimes use: "Absence of evidence is not evidence of absence." Due to all of these factors, a lot of corporate and economic crimes go unpunished while having serious financial repercussions, and white-collar crime is still mainly an unmanaged risk in firms Yang, Su, Wang, & Xu, (2022).…”
Section: Theory Of Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we should remember the adage that scientists who are looking for extraterrestrial life sometimes use: "Absence of evidence is not evidence of absence." Due to all of these factors, a lot of corporate and economic crimes go unpunished while having serious financial repercussions, and white-collar crime is still mainly an unmanaged risk in firms Yang, Su, Wang, & Xu, (2022).…”
Section: Theory Of Powermentioning
confidence: 99%
“…Sociologists are particularly interested in fraud because it reveals a variety of social network characteristics, both good and bad (Iuga et al, 2016). These social networks and linkages have a negative side that increases opportunities for dishonesty, vice, and improper behaviour (Yang, Su, Wang, & Xu, 2022). Inappropriate usage of social networks places a special emphasis on trust and human relationships.…”
Section: (B) Interactionmentioning
confidence: 99%
“…In contrast, Lea et al (2009) assert that prior knowledge is what increases the chance of falling victim, because in the face of such knowledge the victim behaves with less caution. Many times, victims of investment frauds have prior knowledge in the field of financial investment ( Xiao and Porto, 2021 ; Yang et al, 2022 ). Rebovich and Layne (2000) found that victims of investment frauds are more financially literate than the general population.…”
Section: Motives and Circumstances For Becoming Victimmentioning
confidence: 99%
“…Pang et al [18] analyzed and diagnosed the electromagnet manufacturing process based on fuzzy fault trees and evidence theory. Yang et al [19] used models such as fault trees to analyze the spread, identification, and causes of capital-raising frauds. Zhang et al [20] used a fault tree model to analyze the collision risk factors of ship collisions, which can effectively guide rescue efforts.…”
Section: Introductionmentioning
confidence: 99%